Indentured labour - Gokhale, Gopal Krishna 1866-1915 (Adam Matthew Digital, 1912)
Gokhale's speech against sending Indians as indentured labour to other British colonies; from the proceedings of the Council of the Governor General of India for 4 Mar. 1912